Microstructure evolution, densification behavior and mechanical properties of nano-HfB2 sintered under high pressure. Issue 6 (15th April 2019) - Liang, Hao; Guan, Shixue; Li, Xin; Liang, Akun; Zeng, Yan; Liu, Chuanqi; Chen, Haihua; Lin, Weitong; He, Duanwei; Wang, Liping; Peng, Fang
Abstract: A series of pure HfB2 ceramics have been prepared by sintering nano-grained powder using high-energy ball milling at 700–1600 °C and 5.5 GPa. The HfB2 ceramics are characterized via various techniques for their residual stress, grain size, density, microstructures and defects, hardness, fracture toughness, thermal stability, and oxidation resistance. All properties strongly depend on the treatment temperature, but the exact manner of dependence for each property varies. The results identified that the HfB2 ceramic sintered at a relatively low temperature of 1000 °C and 5.5 GPa – a bulk pure nano-grained composite for the first time – has the best overall performance. It has a relative density of 99.6%, a Vickers hardness of 26 GPa, a fracture toughness of 5.2 MPa m 1/2, and excellent thermal stability and oxidation resistance at high temperatures. Additional strengthening and stabilizing effects are provided by microstructures and defects such as large-angle grain boundaries, stacking faults and twinning. Simultaneous high temperature and high pressure is an effective sintering route for HfB2 ceramics with grain-size ranging from nanometer to micron.